Desire to Have Children Among Transgender People in Germany: A Cross-Sectional Multi-Center Study - Auer, Matthias K.; Fuss, Johannes; Nieder, Timo O.; Briken, Peer; Biedermann, Sarah; Stalla, Guenter K.; Beckmann, Matthias; Hildebrandt, Thomas (Journal of Sexual Medicine, 2018)
Many trans individuals undergo medical interventions that result in irreversible loss of fertility. Little is known about their desire to have children and attitudes toward fertility preservation options.To study how the desire for children and the use of fertility preservation options varies among trans women and trans men in different transitioning stages in Germany.In this cross-sectional multi-center study, N = 99 trans women and N = 90 trans men were included. Of these, 26 of each sex were just about to start medical treatment.Outcome parameter were the prevalence and determinants of a desire to have children in trans persons.Before treatment, a desire for children was significantly higher in trans men compared to trans women (P = .016). In contrast, in those who had already started treatment, a current desire to have children was equally present in about one fourth of participants of both genders while the interest in having children in the future was significantly higher in trans women (69.9%) than in trans men (46.9%; P = .034). Although 76.1% of trans women and 76.6% of trans men indicated that they had at least thought about preserving germ cells before starting medical transition, only 9.6% of trans women and 3.1% of trans men had put this idea into practice. Most trans men in both groups indicated that insemination of a female partner with sperm from an unrelated donor was a suitable option to fulfill their child wish, potentially explaining their low interest in preserving their own germ cells. Finally, a logistic regression analysis accounting for potential confounders revealed that overall trans women were more than twice as likely to have a current desire to have children (odds ratio 2.58), and this wish was on average 5.3% lower with each year of increasing age.A low level of fertility preservation among trans persons is contrasted by a high level of desire for children. This highlights the importance of counseling trans individuals regarding fertility preservation options.To our knowledge, this is the first study that addresses desire to have children in a clinical sample of trans women. It is also the first that investigates this issue among trans men who have not started medical treatment, and the first comparison of both genders. A limitation for the generalization of our results is the special legal context in Germany that forbids oocyte donation for reciprocal in vitro fertilization. Reproductive desire is high among trans individuals, but the use of reproductive options is surprisingly low. Auer MK, Fuss J, Nieder TO, et al. Desire to Have Children Among Transgender People in Germany: A Cross-Sectional Multi-Center Study. J Sex Med 2018;15:757-767.
EVALuna2:157267